Factors influencing stroke in Indonesia based on the Indonesia Family Life Survey 5 - Maki Zamzam; Mochammad B. Qomaruddin; Lidia E. Kurniavie; Novera Herdiani (AOSIS, 2023)
Background: Stroke is a fatal and crippling disease that affects more than 15 million individuals globally each year. Stroke can strike anyone, especially people who are exposed to high-risk factors that cause stroke itself. A restriction in blood flow can cause a stroke, a disorder that affects the brain. Objective: This study's objective is to examine the associations between individual characteristics (age and sex), diabetes mellitus, hypertension, coronary heart disease, and smoking with the prevalence of stroke patients. Materials and Methods: This study has a cross-sectional design and is an analytical observational study. Secondary data from the IFLS 5 survey database was used. Stroke was the dependent variable. Diabetes mellitus, hypertension, coronary heart disease, age, gender, and smoking were the independent variables. Stata 13's multiple logistic regression was used to examine the data. Results: The incidence of stroke increased with the age of the subject more than the average age of the overall sample (age ≥39 years old) (OR=0.13; 95% CI=0.08 to 0.20 P0.001), male gender (OR=1.48; 95% CI= 1.07 to 2.03 P=0.017), hypertension (OR=10.53; 95% CI=8.09 to 13.69 P0.001), diabetes mellitus (OR=1.94; 95% CI=1.37 to 2.74 P0.001), coronary heart disease (OR =2.81; 95% CI=1.93 to 4.08 P0.001). Conclusions: Age, gender, diabetes, hypertension, coronary heart disease, and coronary artery disease are all associated with an increased risk of stroke in Indonesia.